Exogenous Progesterone Produces Significant Histomorphological Changes in the Lungs of Experimental BALB/c Mice - Mamoona Shafiq, Erum Afaq, Tooba Zafar, Mehwish Qamar, Saima Qureshi, Amna Faruqi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Progesterone is used in combined oral contraceptive pills and also has its effect on the respective receptors which are responsible for sexual development. Bronchial asthma emerges to be a major health issue in Pakistan with estimated prevalence is about 5% of the total population. Epidemiological studies highlight that one of the considerable risk factor for morbidity and mortality in inflammatory lung diseases is female gender. This suggests that sex-related hormones might play an imperative role in asthma disease progression. Understanding the biological role of sex hormones in regulating airway inflammation is crucial given the rising prevalence of chronic diseases among women worldwide. Aim: To determine the effect of progesterone on lungs of adult male mice by assessing and comparing the histological parameters e.g. bronchiolar smooth muscle size and peri-bronchial lymphocytic infiltration. Study Design: Randomized control trial Place and Duration of Study: Department of Physiology, Islamabad Medical & Dental College Islamabad in collaboration with National Institute of Health Islamabad from 1st October 2018 to 31st July 2019. Methodology: Sixty BALB/c mice were divided into 2 groups and each group comprised 30 mice. Group I (control group) received only distilled water and group 2 (norethisterone BP group) received pills mixed in distal water according to body weight of the mice respectively for 60 days. Results: In response to progesterone, 30% of the total mice had nil, 40% had mild, 26.7% of the total who showed moderate while severe PBLI was observed in 3.3% of the mice. Different frequencies of Bronchiolar Smooth Muscle Hyperplasia were observed when compared to Control group. Mild to moderate hyperplasia was produced by progesterone (norethisterone BP) group. Conclusion: Progesterone is the sexual hormone which modulates inflammatory processes in the lungs producing pulmonary inflammatory responses leading to asthma and also causes hyperplasia of the bronchiolar smooth muscles. Keywords: Progesterone, Asthma, Bronchiolar smooth muscle, Peri-bronchial lymphocytic Infiltration, BALB/c mice